RANCANG BANGUN ROBOT PEMOTONG RUMPUT BERBASIS ATMEL AT89S52 DENGAN SENSOR INFRA RED MENGGUNAKAN BAHASA ASSEMBLER DAN SIMULATOR PROTEUS 8.0 - Rini Nuraini (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Grass is a young plant that grows in the yard of the house, grass plants also require maintenance consisting of three things, namely pruning, fertilizing, and watering. Currently, to carry out manual grass cutting activities, it is very slow, especially in large fields, with technological developments, solutions are needed that can accelerate performance in cutting grass. Mowing can be done quickly and automatically using a variety of electronic components and lawn mowers. This research is part of the development of lawn mower robots that focus on the design of cutting blades. The lawn mower blade was chosen to suit the development design of the lawn mower robot with several criteria, namely light weight, can be driven using a DC motor, can cut grass with low cutting force. The cutting knife has a working width of 20 cm consisting of four blades. The blade is rotated at a speed of 2,500 rpm.